Archaeological and Anthropological Investigation in Case of Urgent Time Constraints of Rescue Archaeology in South Korea. (29th March 2021) - Lee, Hyejin; Song, Mi Kyung; Nam, Kyoung-Mi; Kim, Heeseon; Park, Ji-Won; Cha, Soon Chul; Kim, Jieun; Hong, Jong Ha; Kang, Ryang-Ji; Shin, Dong Hoon
In the general context of rescue archaeology or in any emergency salvage operation, especially where human bones are involved that need to be cremated within a short time frame, anthropologists cannot conduct their work carefully at a university or institute lab. Thus, they have sought ever-more efficient and effective investigative protocols by which work can be conducted in cases of urgent time constraints. A recent anthropological survey conducted at a small town in South Korea (Goryeung) is thus significant. A joint team of anthropologists and dress historians performed collaborative research work in a "field lab" set up at the excavation site. Our novel protocol, by which academic data demonstrably can be successfully secured in the field instead of having to be sent to a university or institute lab, could be useful for the purposes of rescue archaeology.